Vocal Hygiene Training and Mental Well-being in Higher Education Faculty in Pakistan: A pilot Quasi-experimental Study - Shahzadi, Shazia (2026)
University professors are at elevated risk of voice disorders due to sustained, high-intensity vocal demands, which may undermine teaching effectiveness and psychological health. Although vocal hygiene programs are recognized for improving vocal function, their potential impact on mental well-being in higher education faculty remains underexplored. This study examined the effectiveness of a structured vocal hygiene training program on vocal quality and mental health outcomes among professors, with subgroup analysis for pre-existing voice difficulties. A quasi-experimental pretest–posttest control group design was used with 17 full-time faculty members (experimental n = 8, control n = 9). The intervention consisted of three weekly 30-minute sessions covering vocal physiology, recognition of abusive behaviors, and preventive strategies. Outcomes included self-rated vocal quality, listener-rated voice assessments, and Depression Anxiety Stress Scales–12 (DASS-12) scores. Data were analyzed using one-way ANOVA, post hoc Tukey-B, and Cohen’s d effect sizes. No overall group differences were observed in self-rated vocal quality (p = .16). However, professors with pre-existing difficulties in the experimental group improved significantly (gain = +4.00), while those without difficulties declined (gain = −3.00; p = .05). Listener ratings indicated deterioration only in the control subgroup with difficulties (78% preferred pretest recordings, p < .001). Mental health outcomes showed the strongest improvements in the experimental subgroup with difficulties, with large reductions in depression (Δ= −5.6, d = 1.00), anxiety (Δ= −4.5, d = 0.97), stress (Δ= −6.4, d = 1.07), and total DASS-12 scores (Δ= −16.5, d = 1.81). No statistically significant overall group differences were observed.Targeted vocal hygiene training provided substantial benefits for faculty with existing voice problems, improving both vocal quality and psychological well-being. Incorporating vocal health education into faculty development may reduce occupational voice disorders and strengthen resilience in higher education.